The tyrant that lives within us in light of Republic VIII and IX - Montenegro, Maria Aparecida Paiva; Castro, Hedgar Lopes (Revista Archai, 2025)
Hereby we intend to examine the way by which tyranny and the tyrant are presented in Republic, a Platonic dialogue around which we will circumscribe the present study. Our interest emerges from the resurgence, in the 21st century, of democratically elected regimes that, however, flirt with authoritarianism. Socrates’ thesis, presented in Republic VIII (562b-563e), according to which tyranny arises from within democracy, highlights the contradictions inherent in this government regime since its beginnings, helping us to rethink it today. For the purposes of this study we follow the emergence of the issue of tyranny from the first book of the dialogue, until we reach the proper examination of this regime in books VIII and IX, up to which we are faced with the surprising argument that inside each one of us inhabits a sleeping tyrant (Rep.IX, 576b4-6). The city-soul analogy proposed in Republic II, as well as the composite soul thesis in Republic IV work as guiding conceptions of our investigation.